ゼータ関数とイータ関数とガンマ関数

(1)ゼータ関数ととガンマ関数

\[ \zeta(s)=\frac{1}{\Gamma(s)}\int_{0}^{\infty}\frac{x^{s-1}}{e^{x}-1}dx \]

(2)イータ関数とガンマ関数

\[ \eta(s)=\frac{1}{\Gamma(s)}\int_{0}^{\infty}\frac{x^{s-1}}{e^{x}+1}dx \]

(*)

\begin{align*} \int_{0}^{\infty}\frac{x^{s-1}}{e^{x}\pm1}dx & =\int_{0}^{\infty}\frac{x^{s-1}e^{-x}}{1\pm e^{-x}}dx\\ & =\int_{0}^{\infty}x^{s-1}e^{-x}\sum_{k=0}^{\infty}(\mp1)^{k}e^{-kx}dx\\ & =\sum_{k=0}^{\infty}(\mp1)^{k}\int_{0}^{\infty}x^{s-1}e^{-(k+1)x}dx\\ & =\sum_{k=0}^{\infty}(\mp1)^{k}\frac{1}{(k+1)^{s}}\int_{0}^{\infty}y^{s-1}e^{-y}dy\qquad,\qquad y=(k+1)x\\ & =\sum_{k=0}^{\infty}(\mp1)^{k}\frac{1}{(k+1)^{s}}\Gamma(s) \end{align*}

これより、

(1)

\[ \zeta(s)=\frac{1}{\Gamma(s)}\int_{0}^{\infty}\frac{x^{s-1}}{e^{x}-1}dx \]

(2)

\[ \eta(s)=\frac{1}{\Gamma(s)}\int_{0}^{\infty}\frac{x^{s-1}}{e^{x}+1}dx \]

ページ情報

タイトル

ゼータ関数とイータ関数とガンマ関数

URL

https://www.nomuramath.com/krhslkcm/

SNSボタン